Advancements in Materials for 3D-Printed Microneedle Arrays: Enhancing Performance and Biocompatibility - Mahmood Razzaghi; Joel Alexander Ninan; Mohsen Akbari (Micromachines)
The rapid advancement of 3D printing technology has revolutionized the fabrication of microneedle arrays (MNAs), which hold great promise in biomedical applications such as drug delivery, diagnostics, and therapeutic interventions. This review uniquely explores advanced materials used in the production of 3D-printed MNAs, including photopolymer resins, biocompatible materials, and composite resins, designed to improve mechanical properties, biocompatibility, and functional performance. Additionally, it introduces emerging trends such as 4D printing for programmable MNAs. By analyzing recent innovations, this review identifies critical challenges and proposes future directions to advance the field of 3D-printed MNAs. Unlike previous reviews, this paper emphasizes the integration of innovative materials with advanced 3D printing techniques to enhance both the performance and sustainability of MNAs.